2002
DOI: 10.1111/j.1749-6632.2002.tb02787.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantation Defects in Infertile Women with Endometriosis

Abstract: The endometrium undergoes characteristic histologic changes during the menstrual cycle as it prepares for embryo implantation. Historic and current data suggest the presence of a defined period of maximal uterine receptivity during the mid-secretory phase occurring between days 7 and 10 postovulation. In recent years, we and others have sought to define biochemical markers of receptivity that might be used to better understand this time of endometrial differentiation. Based on the work with cell adhesion molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 118 publications
(120 reference statements)
3
55
0
8
Order By: Relevance
“…regulated EGR1, MMP10, stanniocalcin 1 (STC1), ALDH1A1, cadherin 18 and IGFBP3 genes, which are known to be expressed in endometrial stromal cells and involved in endometrial physiology (Aghajanova et al, 2010;Talbi et al, 2006). Moreover, up-regulation in Ishikawa epithelial cells of HOXA10 and osteopontin (Naciff et al, 2010;Smith and Taylor, 2007), which are important for endometrial receptivity in vivo (Daftary and Taylor, 2001;Lessey, 2002), is in line with the current finding of IGFBP1 up-regulation by BPA in human endometrial stromal cells at the same concentration. These data support potential effects of high-dose BPA exposure on endometrial maturation and function, with possible consequences on endometrium-embryo communication.…”
Section: High Doses Of Bpasupporting
confidence: 79%
“…regulated EGR1, MMP10, stanniocalcin 1 (STC1), ALDH1A1, cadherin 18 and IGFBP3 genes, which are known to be expressed in endometrial stromal cells and involved in endometrial physiology (Aghajanova et al, 2010;Talbi et al, 2006). Moreover, up-regulation in Ishikawa epithelial cells of HOXA10 and osteopontin (Naciff et al, 2010;Smith and Taylor, 2007), which are important for endometrial receptivity in vivo (Daftary and Taylor, 2001;Lessey, 2002), is in line with the current finding of IGFBP1 up-regulation by BPA in human endometrial stromal cells at the same concentration. These data support potential effects of high-dose BPA exposure on endometrial maturation and function, with possible consequences on endometrium-embryo communication.…”
Section: High Doses Of Bpasupporting
confidence: 79%
“…Integrins have been proposed to be sensitive indicators of endometrial receptive status and specifically αvβ3 integrin expression has been reported to be reduced in women with endometriosis; thus, that integrin has been proposed as a useful marker of the disease (14,15). However, other authors did not confirm these findings (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In the human endometrium, integrin avb3 exhibits a mid-secretory phase increase of expression influenced by ovarian hormone signaling (Daftary et al, 2002;Lessey, 2002). Indeed, avb3 is up-regulated in immature ovariectomized rats in response to exogenous progesterone, or a combination of estrogen and progesterone, indicating that the epithelial expression of avb3 is regulated, at least in part, by maternal hormones, and progesterone in particular (Srinivasan et al, 2009).…”
Section: Endometrial Integrinsmentioning
confidence: 99%
“…A number of studies have reported that the expression of epithelial avb3 is associated with the window of implantation and that the endometrium is devoid of this particular integrin in certain cases of infertility (Lessey et al, 1992;Castelbaum et al, 1994), endometriosis (Lessey et al, 1994;Lessey, 2002;Wei et al, 2009;Casals et al, 2012), and idiopathic infertility (Lessey et al, 1995). The level of integrin b3 mRNA on day 21 has been suggested as a possible indicator with which to predict success rates following ART, while avb3 has been considered as a clinical biomarker for human implantation (Elnashar and Aboul-Enein, 2004).…”
Section: Endometrial Integrinsmentioning
confidence: 99%
See 1 more Smart Citation